Fast and Ample Light Controlled Actuation of Monodisperse All‐DNA Microgels. (18th February 2021) - Merindol, Rémi; Martin, Nicolas; Beneyton, Thomas; Baret, Jean‐Christophe; Ravaine, Serge
Abstract: The assembly of adaptive hierarchical soft materials that resemble living tissues requires responsive building blocks of controlled dimensions. While DNA self‐assembly provides an exceptional tool for nanoscale architectural control, responsive DNA microstructures remain scarce. Here, two challenges controlling the size of DNA microstructures and embedding them with fast and ample structural response are addressed. For size‐control, arrested phase separation and microfluidic confinement are combined to produce monodisperse all‐DNA particles. For responsiveness, a light controlled coil‐globule transition of the microgel DNA network powered by an azobenzene cationic surfactant is implemented. The photoinduced trans‐cis isomerization of the azobenzene moiety reduces its affinity for DNA which results in fast, large amplitudes microgel swelling. Finally, the assembly of light responsive microgel superstructures is demonstrated as proof‐of‐concept hierarchical all‐DNA materials. Abstract : Phase transition is commonly used to synthesize and actuate synthetic hydrogels. This concept is brought into DNA materials to prepare monodisperse all‐DNA microgels and embed them with light responsive properties. Confined phase separation is used to control the size of the microgels and a photoresponsive surfactant to trigger tenfold swelling within seconds on isolated microgels and periodic superstructures.